Novel equation for skeletal muscle mass estimation is useful for predicting mortality in patients with heart failure. (11th May 2022) - Honma, S; Katano, S; Nagaoka, R; Numazawa, R; Kouzu, H; Ohori, K; Nishikawa, R; Ohwada, W; Nagano, N; Koyama, M; Katayose, M; Kobayashi, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Skeletal muscle mass in heart failure (HF) patients is closely related to exercise tolerance and prognosis. Although the dual-energy X-ray absorptiometry (DEXA) method is a standard method for measuring skeletal muscle mass, it is not suitable in a daily clinical setting since it is a costly and hospital-based modality. We recently reported that an equation for appendicular skeletal muscle mass index (ASMI) estimation using anthropometric parameters predicted DEXA-measured ASMI in HF patients with reasonable accuracy. Here, we examined the prognostic impacts of ASMI predicted by the equation (predicted ASMI) in HF patients. Methods: Data for 539 patients with HF ( 73 ± 14 years old, 43% female) who received the DEXA method and measurements of calf circumference (CC) and mid-arm circumference (MAC) between August 1, 2015, to August 31, 2020, were used for analyses. DEXA measured-appendicular skeletal muscle (ASM) was calculated as the sum of bone-free lean masses in the arms and legs, and ASMI was defined as ASM/height². Predicted ASMI was calculated as we previously reported: predicted ASMI (kg/m²) = [0.214 × weight (kg) + 0.217 × CC (cm) - 0.189 × MAC (cm) + 1.098 (male = 1, female = -1) + 0.576]/height² (m²). Low ASMI was defined as <7.0 kg/m² in males and <5.4 kg/m² in females, respectively. The primary endpoint was all-cause death. Multiple imputation using chained equations was used for the substitution of missing values. Results: The median follow-up period was 1.75 years (interquartile range, 0.96 to 2.37 years), and 73 patients (15%) has died. Kaplan-Meier survival curves showed that patients with low DEXA measured-ASMI and patients with low predicted ASMI had significantly lower survival rates than those with high ASMI (Figure 1). In a multivariate Cox proportional hazard analyses adjusted for age, sex, logarithmic B-type natriuretic peptide, cystatin C based-estimated glomerular filtration rate, and gait speed, DEXA-measured ASMI [hazard ratio (HR), 0.982; 95% confidence interval (CI), 0.967 to 0.988; p<0.001] and predicted ASMI (HR, 0.979; 95% CI, 0.962 to 0.996; p=0.018) were independent predictors of all-cause mortality, respectively. Inclusion of predicted ASMI into the adjustment model improved the accuracy of prediction of the mortality after discharge [continuous net reclassification improvement, 0.338, p<0.01; integrated discrimination improvement, 0.020, p < 0.05] (Figure 2). Conclusions: ASMI estimated by an equation using CC and MAC predicted the prognosis of HF patients at a similar level of accuracy to DEXA-measured ASMI, and it can be applied to the assessment of skeletal muscle mass in a daily clinical setting and in large population-based studies.